After Bali : the threat of terrorism in Southeast Asia - Ramakrishna, Kumar; Tan, See Seng, 1965- (World Scientific ; Institute of Defence and Strategic Studies, 2003)
This book critically analyses the specific threat of terrorism in Southeast Asia since the Bali blasts of 12 October 2002 and the US-led war on Iraq. It offers a comprehensive and critical examination of the ideological, socioeconomic and political motivations, trans-regional linkages, and media representations of the terrorist threat in the region, assesses the efficacy of the regional counter-terror response and suggests a more balanced and nuanced approach to combating the terror threat in Southeast Asia.